Combined effect of creatine monohydrate or creatine hydrochloride and caffeine supplementation in runners’performance and body composition - Santana, Jeferson Oliveira (2018)
Background Creatine monohydrate (CrM) and caffeine are two of the main substances used to enhance athletic performance although some studies say that they impair each other and CrM could promote weight gain. Objective evaluate the association of CrM or creatine hydrochloride (CrHCl) with caffeine (Caf) supplementation on runners' performance and body composition. Methods 16 individuals, both genders (20-30 years) were randomly divided in 3 groups 1) CrM+Caf (n=6), 2) CrHCl+Caf (n=5) and 3) Placebo+Caf (n=5), they did four running sessions per week, during four weeks. Supplementation was given on a double blind manner, CrM+Caf (20g.day-1 per 7 days + 5 g.day-1 per 21 days of CrM), CrHCl+Caf (6g.day-1 per 7 days + 1.5 g.day-1 per 21 days of CrHCl) and Placebo+Caf (20g.day-1 per 7 days + 5 g.day-1 per 21 days of resistance starch). Caffeine ingestion was acutely administered for all groups, 6mg/kg-1 body weight, only in the last day of the experimental protocol. We collected PRE and POST-treatment, body fat (BF), body weight (BW), 10 km time trial (TT), rating of perceived exertion (RPE), delayed onset muscle soreness (DOMS) and gastrointestinal discomfort perception (GDP). Results No differences were found between groups for RPE, DOMS, BF, BW and GDP. TT decreased significantly for CrM+Caf and CrHCl+Caf group, but no for Placebo+Caf. BF decreased significantly in CrHCl+Caf group and lean body mass increased in CrM+Caf and CrHCl+Caf group. Conclusion These data suggest that either CrM or CrHCLsupplementation works synergistically with acute CAF supplementation improving running performance.